2022
DOI: 10.1101/2022.05.03.490475
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Manufacturing CD20/CD19-targeted iCasp9 regulatable CAR-TSCMcells usingqCART, theQuantum pBac-based CAR-T system

Abstract: CD19-targeted chimeric antigen receptor therapies (CAR19) have driven a paradigm shift in the treatment of relapsed/refractory B-cell malignancies. However, >50% of CAR19-treated patients experienced progressive disease mainly due to antigen escape and low persistence. Clinical prognosis is heavily influenced by CAR-T cell function and systemic cytokine toxicities. Furthermore, it remains a challenge to efficiently, cost-effectively, and consistently manufacture clinically relevant number of virally enginee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 48 publications
(113 reference statements)
0
8
0
Order By: Relevance
“…Of note, we observed that increasing the amount of donor DNA (carrying CAR) introduced into CAR-T cells increases integrant copy number in cells. 26 To reduce safety risks, we optimized the concentration of donor DNA such that integrant copy number per cell would be below five, as shown by the low CAR copy numbers found in T cells of both donors (3.08 and 1.68 in donors 1 and 2, respectively; Supplementary Table S2). Interestingly, remarkable conformity was found in the integration profiles of both donor T cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of note, we observed that increasing the amount of donor DNA (carrying CAR) introduced into CAR-T cells increases integrant copy number in cells. 26 To reduce safety risks, we optimized the concentration of donor DNA such that integrant copy number per cell would be below five, as shown by the low CAR copy numbers found in T cells of both donors (3.08 and 1.68 in donors 1 and 2, respectively; Supplementary Table S2). Interestingly, remarkable conformity was found in the integration profiles of both donor T cells.…”
Section: Resultsmentioning
confidence: 99%
“…One possibility is that qBT increased the CD4 CAR + T SCM population (Figure 4C), which in turn enhanced proliferation of CD8 T SCM population without concomitant differentiation. This may reflect the high (3-9) and balanced (approximately 1) 26 CD8:CD4 ratios observed in healthy donors and patients, respectively.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…As demonstrated in another study, this preferential enrichment of CD8 T cells can serve to complement the more difficult-to-enrich patient CD8 T cells and contribute to a balanced CD8/CD4 ratio (approximately 1.0) in CAR-T cells produced from patients with B-cell malignancies. 44 Additionally, CAR-T cell expansion and persistence have emerged as key efficacy determinants in cancer patients, and both are positively correlated with the proportion of T SCM cells in the final CAR-T cell product 50,51 . In line with these findings, we have demonstrated that our qPB-derived CAR-T cells, which are enriched in TSCM cells (especially among CD8 + CAR + T cells), exhibited potent antitumor effects both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%